Automatic Smoke/Forest Fire Detecting System based on Visual IoT - Tungpimolrut, Kanokvate; Karnjana, Jessada; Chatpoj, Montri; Kitbutrawat, Nathavuth; Pavarangkoon, Praphan; Murata, Ken T. (My University, 2025)
In this paper, a visual IoT system or IP camera system for early detection of smoke/forest fire has been investigated. The overall system implementation including hardware and software as well as system installation in targeted areas in Chiangmai, Thailand have been also described. The dataset construction, the preliminary model development and testing have been conducted based on YOLOv5. The model improvement based on Fast Segment Anything Model with YOLOv11 has been proposed to improve False Positive. The results show good performance of Mean Square Error.
Keywords: Forest fire; machine learning; smoke detection